2015
DOI: 10.3354/dao02903
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Tasmanian aquabirnaviruses from 1998 to 2013

Abstract: Tasmanian aquabirnaviruses (TABVs) have been isolated intermittently since 1998 from healthy Atlantic salmon Salmo salar and rainbow trout Oncorhynchus mykiss farmed in Macquarie Harbour, Tasmania, Australia. However, beginning in 2011, TABVs have been isolated from rainbow trout in association with mortality events. To determine if recent molecular changes in TABV were contributing to increased mortalities, next generation sequencing was undertaken on 14 TABVs isolated from 1998 to 2013. Sequencing of both ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Although for some authors VP5 activity does not depend on its size, and even though apoptosis is not dependent of that protein [54,57,108], others defended the anti-apoptotic activity of the protein [52] and stated that a deletion in the 15 kDa normal VP5 protein might affect its activity and, therefore, viruses expressing a truncated 12 kDa VP5 should be more benign. To this regard, Davies et al [99] noted that all the Australian strains from healthy fish that they sequenced had a deletion at the N-terminal; however, other authors found that differences in VP5 size in field isolates were not related to the level of disease [79,109]. In IBDV, a clear association between the size of the protein and the virulence of the strain has been demonstrated in field isolates [61]; thus, the very virulent IBDV strains exhibit a large ORF and the low virulent ones have shorter forms.…”
Section: Is Vp5 Expression a Determinant Of Virulence?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although for some authors VP5 activity does not depend on its size, and even though apoptosis is not dependent of that protein [54,57,108], others defended the anti-apoptotic activity of the protein [52] and stated that a deletion in the 15 kDa normal VP5 protein might affect its activity and, therefore, viruses expressing a truncated 12 kDa VP5 should be more benign. To this regard, Davies et al [99] noted that all the Australian strains from healthy fish that they sequenced had a deletion at the N-terminal; however, other authors found that differences in VP5 size in field isolates were not related to the level of disease [79,109]. In IBDV, a clear association between the size of the protein and the virulence of the strain has been demonstrated in field isolates [61]; thus, the very virulent IBDV strains exhibit a large ORF and the low virulent ones have shorter forms.…”
Section: Is Vp5 Expression a Determinant Of Virulence?mentioning
confidence: 99%
“…Similarly, Santi et al [80], working with nine strains of type L or H, did not consider the minor differences encountered in VP1, VP3, and VP4 as candidates to be determinants, and only pointed to specific positions in VP2 and the size of VP5. More recently, Mohr et al [109] reported that, in the appearance of virulent IPNV strains from previous isolates causing no disease in Tasmanian rainbow trout farms, only a change in VP3 was common between the isolates; however, since until then "substitutions in VP3 . .…”
Section: Other Viral Proteins and Their Interactions Are Also Determimentioning
confidence: 99%
“…La primera clasificación filogenética fue propuesta por Blake et al (2001), donde se describió la presencia de 6 genogrupos, compuestos por diferentes cepas de origen europeo, americano y asiático. Posteriormente, Nishizawa et al (2005) revelaron la existencia de un séptimo genogrupo integrado únicamente por cepas japonesas, y recientemente en Australia se aisló un nuevo Aquabirnavirus desde trucha arcoíris, que fue clasificado en un octavo genogrupo (McCowan et al, 2015;Mohr et al, 2015). En Chile, los virus IPN que han sido caracterizados genéticamente pertenecen a los Genogrupos 1 y 5, i.e., norteamericanos y europeos, respectivamente (Eissler et al, 2011;Mutoloki & Evensen, 2011;Calleja et al, 2012;Tapia et al, 2015;Jorquera et al, 2016), dentro de los cuales forman sus propios subtipos o subgrupos (Tapia et al, 2015).…”
unclassified
“…For the two samples from 2017 and 2018, RNA was isolated from plasma, and RNA was sequenced using on the Illumina HiSeq 4000 system. In the case of the sample of 1995, RNA was extracted from serum, but here a sequencing independent single-primer amplification (SISPA) method was used previous to library construction [ 27 ] and sequencing in Illumina MiSeq.…”
Section: Resultsmentioning
confidence: 99%